Migration as Feminisation? Chinese Women's Experiences of Work and Family in Australia. - Ho, Christina (Journal of Ethnic & Migration Studies, 2006)
Like many Western governments, the Australian government increasingly views migration through the lens of economic efficiency, arguing that skilled professionals achieve the best employment outcomes and therefore constitute the ideal migrant. This paper challenges these claims, showing that skilled migrants do not always successfully transfer their skills to new labour markets. It argues that the government's ‘success story’ narrative disguises a much more complex reality, in which migrants’ employment outcomes are shaped by broader social and cultural factors, as well as just economic ones. In particular, it shows that men and women typically experience migration differently, and the challenges of re-negotiating work and care in a new setting often lead to a ‘feminisation’ of women's roles, as they find themselves taking up more traditional gender roles as wives and mothers. Using in-depth interviews with Chinese women and survey data from the Australian government, I show that, in Australia, migrant women often experience downward occupational mobility and a re-orientation away from paid work and towards the domestic sphere.